Utilisation of Social Media tools to enhance knowledge sharing practices among knowledge workers at the Nelson Mandela African Institution of Science and Technology in Arusha, Tanzania - Schutte, Marietjie (University of Pretoria, 2017)
Mini Dissertation (MIT)--University of Pretoria, 2014.